Mapping of pga value using psa method in West Halmahera North Maluku - Rohima Wahyu Ningrum; Wiwit Suryanto; Hendra Fauzi; Estuning Tyas Wulan Mei (Jurnal Teknosains, 2020)
The earthquake that occurred in the West Halmahera region was very detrimental, even though the human casualties were not very significant. But it will affect the stability and capacity of a region in terms of regional development. The mapping of earthquake-prone areas is carried out by a probabilistic seismic hazard analysis (PSHA) method to analyze soil movement parameters, namely Peak Ground Acceleration so that it can determine earthquake-prone areas in West Halmahera. The results of seismic hazard analysis show that the West Halmahera area is an area that is relatively prone to earthquake hazards because it is still strongly influenced by subduction (megathrust) earthquakes from the Philippine plate, Maluku sea and Sangihe. This is indicated by the value of earthquake acceleration on the Peak Ground Acceleration for the 500 year return period of around 0.38 - 3.69 g and 0.30 - 3.69 g for the 2500 year return period.